2023
DOI: 10.3390/md21020064
|View full text |Cite
|
Sign up to set email alerts
|

Dinophysis acuminata or Dinophysis acuta: What Makes the Difference in Highly Stratified Fjords?

Abstract: Dinophysis acuminata and D. acuta, which follows it seasonally, are the main producers of lipophilic toxins in temperate coastal waters, including Southern Chile. Strains of the two species differ in their toxin profiles and impacts on shellfish resources. D. acuta is considered the major cause of diarrhetic shellfish poisoning (DSP) outbreaks in Southern Chile, but there is uncertainty about the toxicity of D. acuminata, and little information on microscale oceanographic conditions promoting their blooms. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…By the end of summer 2020, a moderate-density population of Karenia spp. (>10 5 cells L −1 ) was fortuitously detected in samples from Pitipalena Fjord collected during a 24 h study focused on Dinophysis [ 56 ]. Here, for the first time in Chile, the microscale distribution of Karenia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By the end of summer 2020, a moderate-density population of Karenia spp. (>10 5 cells L −1 ) was fortuitously detected in samples from Pitipalena Fjord collected during a 24 h study focused on Dinophysis [ 56 ]. Here, for the first time in Chile, the microscale distribution of Karenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the natural barrier seems to be the isohaline of 21, i.e., the presence of EFW. In an earlier study, we concluded that the presence of EFW was a salinity barrier preventing the development of D. acuta in the northern Patagonian fjords [ 56 ]. During the present survey, D. acuta only appeared, briefly, when the warmer and saltier water (ESW) was at the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impacts of climate variability on the multi-decadal fluctuations in the composition and abundance of different functional groups, and on their respective trophic levels, have been the focus of attention in recent decades, due to the threat of climate change and global warming [ 36 ]. The effects will be exacerbated in highly heterogeneous systems such as the Patagonian fjords, where multiple niches promote the development or aggregation of different species, including microalgae [ 37 , 38 ]. Long-term variations in some phytoplanktonic species have been associated with anomalous oceanographic events that occur periodically over decadal time scales [ 39 ].…”
Section: Climate Modulation: a Global Phenomenon Affecting Microalgal...mentioning
confidence: 99%
“…australis (2 × 10 6 cells L −1 ), and resulted in intense brown patches in waters close to the head of the fjord, as well as the death of juvenile hake. Given the niche differences of these HAB species [ 37 , 38 ], while the event was highly anomalous, the potential for its recurrence, and the consequences thereof, cannot be ignored.…”
Section: Extreme Hab Events In Chilean Patagoniamentioning
confidence: 99%